2020
DOI: 10.1016/j.bja.2019.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects in anaesthesia training in Australia and New Zealand

Abstract: Background: Women face gender-based challenges in their medical education and career. Inequitable access to procedural training, a confidence gap, and professional identity deficit have been shown. We made a gender comparison of procedural case volume, confidence for independent practice, perceived gender and ethnic bias, and professional identity in Australasian anaesthesia trainees. Methods: An online, voluntary, anonymous survey using SurveyMonkey® was delivered to Australasian anaesthesia trainees. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
13
2
Order By: Relevance
“…Finally, our results indicate that higher percentage of female team members may improve efficiency, and possibly also global team performance, in simulated difficult airway situations. These findings contrast and extend previous reports, and motivate further efforts to evaluate sex effects in anesthesia simulation studies 38–41 …”
Section: Discussioncontrasting
confidence: 43%
“…Finally, our results indicate that higher percentage of female team members may improve efficiency, and possibly also global team performance, in simulated difficult airway situations. These findings contrast and extend previous reports, and motivate further efforts to evaluate sex effects in anesthesia simulation studies 38–41 …”
Section: Discussioncontrasting
confidence: 43%
“…There are few additional studies of gender bias in the evaluation of anesthesia trainees. However, a recent study of 356 anesthesia trainees in Australia and New Zealand demonstrated that men were significantly more likely to rate their competency above their level of training and exaggerate their procedural experience ( 19 ). If also true in our setting, men’s confidence, particularly regarding procedures, may be viewed more favorably by evaluators and may lead to more outstanding ratings.…”
Section: Discussionmentioning
confidence: 99%
“…In anaesthesia, an Australian study demonstrated male trainees were more likely to rate themselves at a training level higher than their actual level of training and exaggerate procedural experience to supervisors. The authors outlined this could lead to male trainees being afforded a higher level of autonomy of practice and thus a greater number of solo cases than female counterparts [14]. There is evidence this may happen in surgical specialties [15, 16].…”
Section: Gender and The Female Medical Workforcementioning
confidence: 99%